Exogenous Melatonin Boosts Heat Tolerance in Rosa hybrida via RhCOMT1 Modulation - Chenyang Li; Zhiyin Ding; Zipeng Cai; Yongying Ruan; Peitao Lü; Yang Liu (Plants)
Rosa hybrida is one the most commonly cultivated ornamental plant of economic importance and faces major challenges under heat stress. Melatonin has been widely shown to regulate plant stress response; however, the exact mechanism involved in heat stress in R. hybrida has yet to be determined. Here, we observed that R. hybrida in vitro plantlets supplemented with melatonin in the culture medium exhibited higher chlorophyll content, relative ion leakage, and fresh weight after 12 d of high-temperature treatment; the optimal concentration was established at 5 mg/L. Using molecular and biochemical techniques, we explored the roles of a melatonin synthase gene RhCOMT1, which expression was influenced by heat stress and melatonin. RhCOMT1 was located in the nuclear-cytoplasmic under ambient conditions, while heat stress translocated the distribution of RhCOMT1 to chloroplasts. Overexpression of RhCOMT1 in rose petal enhanced thermotolerance, and silencing of RhCOMT1 reduced thermotolerance via affect H2O2 content and relative ion leakage. These findings collectively emphasize the pivotal role of melatonin in enhancing thermotolerance to R. hybrida by alleviation of oxidative stress, through modulation of RhCOMT1 expression and location.